Partial Body Weight-Supported Treadmill Training Versus Isokinetic Training on Muscle Strength and Balance in Children with Hemiparetic Cerebral Palsy: A randomized Controlled trial - Sherief, Abdel Aziz A.; Abogazya, Amr A.; ElAziz, Heba Gaber Abd (International Journal of Psychosocial Rehabilitation, 2020)
--Muscle weakness in children with hemiparetic cerebral palsy is one of the serious complications which affect their performance. Isokinetic is one method to Strength weak muscles in children with hemiplegia and also one of the new applications of decreased weight to achieve muscle strength and function is partial body weight supported treadmill training. To compare between the effect of partial body weight-supported treadmill training and isokinetic training on muscle strength and balance in children with hemiparetic cerebral palsy. Thirty children with hemiparetic cerebral palsy participaed in this study. They aged from 10 to 14 years old. Children were randomly assigned to group A or group B. Children in both groups received the same designed physical therapy program. In addition, group A received partial body weight-supported treadmill training while group B received strength training program for the knee flexor muscle group three sessions per week for 12 successive weeks. Muscle strength and balance were assessed before and after treatment by using the Biodex isokinetic system and Bruininks–Oseretsky Test of Motor Proficiency respectively. The post treatment results revealed significant difference in all measured variables (peak torque and balance) as compared with its pre-treatment results. Post-treatment values measured variables, between the two groups, revealed significant difference in favor of group B. According to current results isokinetic strength training program is likely more effective than partial body weight-supported treadmill training on improving muscle strength and balance in children with hemiparetic cerebral palsy.